2011
DOI: 10.1111/j.1528-1167.2011.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the ketogenic diet in Scn1a mutant mice

Abstract: Summary Purpose We evaluated the ability of the ketogenic diet (KD) to improve thresholds to flurothyl-induced seizures in two mouse lines with Scn1a mutations: one that models Dravet syndrome (DS) and another that models genetic (generalized) epilepsy with febrile seizures plus (GEFS+). Methods At postnatal day 21, mouse models of DS and GEFS+ were fasted for 12–14 hours and then placed on either a 6:1 KD or a standard diet (SD) for two weeks. At the end of the two-week period, we measured thresholds to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 44 publications
6
31
0
1
Order By: Relevance
“…There is strong evidence that the KD effectively controls seizures in patients with DS (Caraballo, 2011;Caraballo et al, 2005;Kang et al, 2005;Korff et al, 2007;Laux and Blackford, 2013), especially when added to the gold standard triple combination (Nabbout et al, 2011). Further, the diet has been reported to exhibit neuroprotective effects (Dutton et al, 2011;Luan et al, 2012) and to control long lasting SE refractory to conventional AED treatment (Nabbout et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…There is strong evidence that the KD effectively controls seizures in patients with DS (Caraballo, 2011;Caraballo et al, 2005;Kang et al, 2005;Korff et al, 2007;Laux and Blackford, 2013), especially when added to the gold standard triple combination (Nabbout et al, 2011). Further, the diet has been reported to exhibit neuroprotective effects (Dutton et al, 2011;Luan et al, 2012) and to control long lasting SE refractory to conventional AED treatment (Nabbout et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…In the N1417H SCN1A rat, methylphenidate inhibited thermally induced seizures and improved hyperactivity and spatial learning (Ohmori et al 2014). Ketogenic diet improved flurothyl seizure thresholds in the heterozygous SCN1A KO and R1648H mice (Dutton et al 2011). Genetic ablation of tau protein in the R1407X KI mouse reduced mortality and epilepsy severity, suggesting that targeting this pathway might be of benefit (Gheyara et al 2014).…”
Section: Dravet Syndrome Genetic Epilepsies With Febrile Seizuresmentioning
confidence: 99%
“…MAD is a modified form of ketogenic diet. The ketogenic diet was showed to improve the seizure thresholds in mice with SCN1A mutation which is the major cause of Dravet syndrome [14]. Previous studies demonstrated a significant reduction of seizure frequency in patients with Dravet syndrome who were maintained on this diet [15,16].…”
Section: Discussionmentioning
confidence: 97%